Jury Commissioner Carl Hernandez's Retirement Dinner at Fresno County Plaza Ballroom - Watkins, Howard::::::::: (1988)
?speaking at lectern with Carl Hernandez, Fred Yamamoto, and Judge Mario Olmos seated